FRAMING DAN LITERASI KRITIS ISU PENDIDIKAN DALAM KONTEN YOUTUBE NAJWA SHIHAB : STUDI PADA PROGRAM MATA NAJWA DALAM LANSKAP MEDIA DIGITAL - Chelsea Febriyanti Putri; Lukman Hakim; Yuna Nazzilla May Firnanda; Salwa Ahmada Febrian; Rafaya Nikmatu Zhahroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the growing role of digital media in shaping public understanding of educational issues and the increasing importance of critical literacy in the information age. The Mata Najwa program on YouTube has become one of the prominent media platforms that actively discuss various educational issues and potentially influence public perception through framing processes. This study aims to analyze the framing of educational issues in Mata Najwa’s YouTube content and examine its contribution to the development of critical literacy among society. A descriptive qualitative approach was employed using Robert N. Entman’s framing analysis model, which consists of four elements: define problems, diagnose causes, make moral judgments, and treatment recommendations. Primary data were obtained from Mata Najwa episodes focusing on educational themes, while secondary data were collected from scholarly journals, books, and other academic sources. The findings reveal that Mata Najwa frames education as a multidimensional issue encompassing unequal access to education, technological readiness, the relevance of education to the labor market, and the challenges of digital transformation. The program identifies structural and social factors as the primary causes of educational problems while emphasizing education as a fundamental right that fosters character development and critical thinking. The proposed solutions include strengthening digital literacy, enhancing teachers’ competencies, updating curricula, and promoting the responsible use of technology. These findings indicate that Mata Najwa applies a critical, educational, and constructive framing approach that contributes to improving public critical literacy regarding educational issues in the digital era.